Comparative analysis of reference evapotranspiration with empirical methods in the Mosna river basin (Aporte Santiaguino, 2024)
The accurate estimation of the reference evapotranspiration (ETo) is a fundamental factor for the planning and management of water resources. The Penman-Monteith method recommended by the FAO is globally accepted as the standard method for calculating ETo, however, this method requires various meteorological parameters, which are generally not found in meteorological stations. In this context, the objective of this research was to evaluate the performance of three empirical methods with respect to the reference method in the Mosna river basin. Daily data provided by SENAMHI and NASA POWER were used in the study. The empirical methods of Hargreaves - Samani, Thornthwaite and Turc underestimated ETo by 1.2%, 56% and 45% compared to Penman-Monteith. Only the Hargreaves – Samani method showed good performance of the ETo with respect to Penman-Monteith evaluated by the test statistics of R2 of 0.86, EPCM of 0.006, RECM of 0.080 and NSE of 0.975. Therefore, the Hargreaves – Samani method that requires only temperature as input can be used in this basin.Keywords: water resource; reference evapotranspiration; Penman-Monteith; Hargreaves-Samani; Mosna River
Keywords: Water resource; Reference evapotranspiration; Penman-Monteith; Hargreaves-Samani; Mosna River